The association of genes involved in the angiogenesis‐associated signaling pathway with risk of anterior cruciate ligament rupture. Issue 12 (11th August 2014) - Rahim, Masouda; Gibbon, Andrea; Hobbs, Hayden; van der Merwe, Willem; Posthumus, Michael; Collins, Malcolm; September, Alison V.
ABSTRACT Angiogenesis‐associated signaling is a fundamental component in the remodeling of the extracellular matrix in response to loading. Genes encoding protein components within this signaling cascade are therefore suitable candidates for investigation into ACL injury susceptibility: namely, vascular endothelial growth factor A isoform (VEGFA), kinase insert‐domain receptor (KDR), nerve growth factor (NGF), and hypoxia inducible factor‐1α (HIF1A). A case‐control genetic association study was conducted on 227 asymptomatic control participants and 227 participants with surgically diagnosed ACL ruptures of which 126 participants reported a non‐contact mechanism of rupture. All participants were genotyped for seven polymorphisms within the four genes. The VEGFA rs699947 CC genotype (p = 0.010, OR: 1.92, 95% CI: 1.17–3.17) was significantly over‐represented within participants with non‐contact ACL ruptures. The VEGFA rs1570360 GA genotype was significantly over‐represented in the CON group (p = 0.007, OR: 1.70, 95% CI: 1.16–2.50). Furthermore, the KDR rs2071559 GA genotype was significantly over‐represented in the female controls (p = 0.023, OR: 2.16, 95% CI: 1.11–4.22). Inferred haplotype analyses also implicated genomic regions spanning the VEGFA and KDR genes. These novel findings suggest that regions within VEGFA and KDR may be implicated in the pathophysiology of ACL ruptures; highlighting the potential biological significance of angiogenesis‐associated signaling in the aetiology of ACL ruptures. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1612–1618, 2014.